2002
DOI: 10.1001/archopht.120.5.554
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Infection, Bcl-2, p53 Protein, and Ki-67 Analysis in Ocular Surface Squamous Neoplasia

Abstract: Objectives:To determine the age and human immunodeficiency virus (HIV) status of patients with ocular surface squamous neoplasia (OSSN), and to analyze tumor proliferation, Bcl-2, and p53 oncoprotein expression in OSSN. Methods:Only patients with histologically proved neoplasia were included in this study. The HIV status was obtained only with informed consent. Monoclonal antibodies to p53 and Bcl-2 protein were used after microwave antigen retrieval to enhance immunohistochemical staining of the sections. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 19 publications
2
39
0
1
Order By: Relevance
“…Similarly, another study in United Kingdom showed that the 77% were male, being 69% of them older than 60 years (McKelvie et al, 2002). Nevertheless, a study in Zimbabwe found that a 70% of patients were young women with a mean age of 35 years (Pola et al, 2003), while in South Africa mean age was 37 years (Mahomed & Chetty, 2002). A study in Tanzania showed that the 45.8% of 168 conjunctival biopsies were OSSN (Poole, 1999).…”
Section: Incidencementioning
confidence: 96%
“…Similarly, another study in United Kingdom showed that the 77% were male, being 69% of them older than 60 years (McKelvie et al, 2002). Nevertheless, a study in Zimbabwe found that a 70% of patients were young women with a mean age of 35 years (Pola et al, 2003), while in South Africa mean age was 37 years (Mahomed & Chetty, 2002). A study in Tanzania showed that the 45.8% of 168 conjunctival biopsies were OSSN (Poole, 1999).…”
Section: Incidencementioning
confidence: 96%
“…Подобные данные получили A. Mahomed и R. Chetty в 2002г. -средний возраст заболевших составил 37 лет [9]. Со-гласно исследованиям K. Toopalli et al, опу-бликованным в 2014 году, СНГП развивается чаще у мужчин (60%) в возрасте 46 лет (minmax 7-85) [10].…”
Section: эпидемиологияunclassified
“…Similar to cancer of the cervix, it has a relatively high rate of recurrence after treatment and may metastasize (Munoz et al, 2003). OSSN has gained interest in the past few years in its association with the HIV-1 pandemic and its increase in incidence is collinear with the increase in HIV-1 (Mahomed & Chetty, 2002). Prior to the HIV-1 pandemic, OSSN was noted to occur predominantly in the elderly for whom it is the third most common oculoorbital tumor after melanoma and lymphoma (Basti & Macsai, 2003;Lee & Hirst, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the HIV-1 pandemic, OSSN was noted to occur predominantly in the elderly for whom it is the third most common oculoorbital tumor after melanoma and lymphoma (Basti & Macsai, 2003;Lee & Hirst, 1997). Previously in addition to advanced age and male sex, other risk factors linked to its pathogenesis had included ultraviolet light B rays and mutation of the p53 tumor suppressor gene (Kestelyn, Stevens, Ndayambaje, Hanssens, & van de Perre, 1990), immunosuppression in organ transplant recipients (Spitzer et al, 2008), cigarette smoking, and in some settings, HPV infection (Mahomed & Chetty, 2002;McDonnell, McDonnell, Mounts, Wu, & Green, 1986). In Africa, OSSN is becoming more common, more aggressive and affects mainly young people, especially females (Kestelyn et al, 1990).…”
Section: Introductionmentioning
confidence: 99%